Tata Kelola Interoperabilitas Data Bantuan Sosial di Dinas Sosial Kota Mojokerto:Perspektif Governance Rhodes - Clarissa Anggi Kusuma; Dian Wijaya; Santosa Santosa (International Forum of Researchers and Lecturers, 2026)
This study examines the management of social assistance data interoperability at the Social Affairs Office of Mojokerto City as an effort to ensure accurate targeting of social assistance distribution. The study aims to analyze the management of social assistance data interoperability from the perspective of Rhodes' Governance theory. This research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The findings indicate that the management of social assistance data interoperability has implemented the principles of network governance through collaboration among the Social Affairs Office of Mojokerto City, the Ministry of Social Affairs, village administrations, neighborhood and community associations (RT/RW), Subdistrict Social Welfare Workers (TKSK), Family Hope Program (PKH) facilitators, field surveyors, and the community. Data interoperability is supported by the utilization of the National Integrated Socio-Economic Data (DTSEN), the use of the National Identification Number (NIK) as the primary identifier, and the implementation of tiered verification and validation processes. However, delays in data updating and suboptimal inter-agency coordination remain major challenges in ensuring accurate targeting of social assistance. The study concludes that strengthening stakeholder collaboration, improving system interoperability, and conducting continuous data updates are essential to support more effective and well-targeted social assistance data governance.